Differences of Visual, Auditorial, Kinesthetic Students in Understanding Mathematics Problems - Sulisawati, Dwi Noviani; Lutfiyah, Lutfiyah; Murtinasari, Frida; Sukma, Luzainiatus (Universitas Malikussaleh, Aceh Utara, Indonesia, 2019)
Characteristics of students who are diverse, such as different learning styles will also lead to the possibility of differences in students' ability to understand the learning material and every problem given, especially at the stage of understanding the problem given, because this stage is the most important step to determine the next problem-solving step. Therefore this study aims to reveal and illustrate how different characteristics of visual, audio and kinesthetic students in understanding problems. Data retrieval was done in class VIII of Arjasa 1 Junior High School with test methods, interviews, and questionnaires. Data were analyzed through stages of data reduction, analysis, and decision making. Furthermore, based on the data analysis that has been done, it can be concluded that there are differences in the characteristics of understanding problems for visual, auditory and kinesthetic students in terms of completeness and regularity of information writing, quantity of repetition of reading questions, marking important information and activity/movement habits done during the process of understanding the problem.